2018
DOI: 10.4314/ijmu.v13i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hyperuricemia and lipid profile in untreated dyslipidemic patients

Abstract: There are a number of epidemiological studies that suggest the association of cardiovascular diseases and uric acid but very few studies highlight the direct association of deranged lipid profile with uric acid levels. The present study was indented to find out if any association exists between hyperuricemia and dyslipidemia. Blood samples were collected from healthy controls (n=70) and patients with dyslipidemia (n=70) who were not receiving any treatment for dyslipidemia. These samples were processed for est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Regarding lipid profile, our results showed that SUA had a positive correlation with TC, TG and LDL-C, and a negative correlation with HDL-C, implying its association with dyslipidemia which was also described by other studies 43,44 . These effects are mainly attributed to the role uric acid plays in regulating fructokinase expression in hepatocytes, leading to an enhanced lipogenic impact of fructose.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding lipid profile, our results showed that SUA had a positive correlation with TC, TG and LDL-C, and a negative correlation with HDL-C, implying its association with dyslipidemia which was also described by other studies 43,44 . These effects are mainly attributed to the role uric acid plays in regulating fructokinase expression in hepatocytes, leading to an enhanced lipogenic impact of fructose.…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence uric acid in Indonesia 18%. 5 Previous study in Korea that average rate of hypercholesterolemia 36%. 7 Study in China 8 that range of risk factors mortality of elderly including obesity, hyperglycemia, high blood pressure, high triglycerides, and cholesterol.…”
Section: Introductionmentioning
confidence: 98%
“…The incidence of uric acid up to 46% and is predicted in 2030 th to 8 million people. 4 Prevalence uric acid in Asia regions total of 24 countries, that the lowest Papua New Guinea 1% and highest Marshall Islands 85% 5 . Study in Sydney 6 Australia that prevalence of hyperuricemia was 22.2%.…”
Section: Introductionmentioning
confidence: 99%